The Mesozoic family Mesoserphidae and its phylogeny (Hymenoptera: Apocrita: Proctotrupoidea). (3rd August 2017) - Li, Longfeng; Rasnitsyn, Alexandr P.; Shih, Chungkun; Ren, Dong
Abstract : Eighteen new species within nine genera, six of which are new, of the Mesozoic hymenopteran family Mesoserphidae are described from the Lower Cretaceous Yixian Formation at Huangbanjigou, Liaoning, and from the latest Middle Jurassic Jiulongshan Formation at Daohugou, Inner Mongolia, China: Mesoserphus venustus sp. nov., Sinoserphus grossus sp. nov., S. flexilis sp. nov., S. petilus sp. nov., Novserphus ningchengensis gen. et sp. nov., Apiciserphus augustus gen. et sp. nov., Amboserphus tumidus gen. et sp. nov., A. beipiaoensis sp. nov., A. dimidius sp. nov., Choriserphus bellus gen. et sp. nov., C. gigantus sp. nov., Basiserphus loculatus gen. et sp. nov., B. longus sp. nov., Ozososerphus lepidus gen. et sp. nov., O. ovatus sp. nov., O. cuboidus sp. nov., Karataoserphus adaequatus sp. nov. and K. gracilentus sp. nov. Two taxonomic changes are proposed, Karataoserphus sinicus (Ping) comb. nov. and Beipiaoserphus meridionalis (Rasnitsyn) comb. nov. In addition, Turgoserphus Rasnitsyn, 1990, Otlia J. F. Zhang, 1992, Oxyuroserphus Rasnitsyn, 1994 and Codoserphus Shi et al .2013 should be considered family incertae sedis due to their hind wings lacking clear diagnostic venation and ovipositor possibly internalized. A key to the genera of Mesoserphidae is provided and morphological classification characters are summarized. Phylogenetic analysis using 22 morphological characters, 18 mesoserphid ingroups and two outgroups indicate that the subfamilies Mesoserphinae and Karataoserphinae should be abandoned. Basal mesoserphids originated in north-eastern China and subsequently spread to other regions. Species of Mesoserphidae with forewing venational pattern of 'type aa' existed from the Middle Jurassic to the Early Cretaceous. http://zoobank.org/urn:lsid:zoobank.org:pub:2F8A0A38-910B-4855-8E43-454603FD4060